2022
DOI: 10.1039/d2se00653g
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-assisted co-exfoliation of graphene nanoplatelets/MoS2for high-performance supercapacitors

Abstract: Co-exfoliated GNP/MoS2 was synthesized in one step and used for supercapacitor study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…There is no significant loss observed with 99.99% retention of its initial specific capacitance, indicating superior rate capability and sustainability of the electrode material, that is, CoNi nanoflowers. [73,74] These results verify that the synthesized material has excellent cyclic stability after 10 000 cycles. The primary reason to get such excellent cyclic retention is due to the interconnected CoNi nanoflowers which facilitated a shorter diffusion path length and succeeded in readily electrolyte penetration.…”
Section: Electrochemical Studies and Effect In Different Electrolyte ...supporting
confidence: 67%
“…There is no significant loss observed with 99.99% retention of its initial specific capacitance, indicating superior rate capability and sustainability of the electrode material, that is, CoNi nanoflowers. [73,74] These results verify that the synthesized material has excellent cyclic stability after 10 000 cycles. The primary reason to get such excellent cyclic retention is due to the interconnected CoNi nanoflowers which facilitated a shorter diffusion path length and succeeded in readily electrolyte penetration.…”
Section: Electrochemical Studies and Effect In Different Electrolyte ...supporting
confidence: 67%
“…19 Further, the MOFs derived hierarchical carbon-based hybrid structures as electrocatalysts for energy conversion systems because they expose more active sites for the adsorption of reactive species and better durability under harsh conditions and subsequent electrocatalytic processes. 20−23 However, researchers explored various affordable electrode materials such as graphene/MoS 2 , 24 conducting polymers, 25 metal oxides, 26 MOFs, coordination polymers, and covalent organic frameworks which are used to improve the efficiency of electrocatalysts and supercapacitor electrodes with high durability. 27 Yu et al utilized a pristine Cu coordination polymer for a supercapacitor with higher specific capacitance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, researchers explored various affordable electrode materials such as graphene/MoS 2 , conducting polymers, metal oxides, MOFs, coordination polymers, and covalent organic frameworks which are used to improve the efficiency of electrocatalysts and supercapacitor electrodes with high durability . Yu et al.…”
Section: Introductionmentioning
confidence: 99%
“…16−19 For example, Han et al 20 designed an independent core−shell heterostructure supported on carbon nanotube fibers by anchoring MoS 2 nanosheets on nanowires (MoS 2 @TiN/CNTF) as the anode of AASCs, which has great advantages in wearable water-based SCs. Abbas et al 21 reported "one-step" liquid phase coexfoliation of graphene (G) and MoS 2 together, i.e., graphene nanoplatelet (GNP)/MoS 2 using high-temperature ultrasonication and gelatin. GNP/MoS 2 nanosheets showed specific capacitance and excellent cycling stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…MoS 2 /C with monolayers has been proven to be a promising material for a wide range of energy storage applications including supercapacitors (SCs) and secondary batteries. SCs combine the technical characteristics of common capacitors and secondary batteries, providing higher specific energy than common capacitors, higher specific power than secondary batteries, and longer cycle life. For example, Han et al designed an independent core–shell heterostructure supported on carbon nanotube fibers by anchoring MoS 2 nanosheets on nanowires (MoS 2 @TiN/CNTF) as the anode of AASCs, which has great advantages in wearable water-based SCs. Abbas et al reported “one-step” liquid phase coexfoliation of graphene (G) and MoS 2 together, i.e., graphene nanoplatelet (GNP)/MoS 2 using high-temperature ultrasonication and gelatin. GNP/MoS 2 nanosheets showed specific capacitance and excellent cycling stability.…”
Section: Introductionmentioning
confidence: 99%